A compression system for studying depth-dependent mechanical properties of articular cartilage under dynamic loading conditions. (October 2018) - Komeili, Amin; Abusara, Ziad; Federico, Salvatore; Herzog, Walter
Highlights: The full thickness of cartilage sample was imaged. Axial strain distribution was quantified in the dynamic state during the compression. Axial strain distribution was more uniform in the dynamic state compared to the static state. Local axial strains increased during the stress relaxation. Abstract: The biological activities of chondrocytes are influenced by the mechanical characteristics of their environment. The overall real-time mechanical response of cartilage has been investigated earlier. However, the instantaneous local mechano-biology of cartilage has not been investigated in detail under dynamic loading conditions. In order to address this gap in the literature, we designed a compression testing device and implemented a dual photon microscopy technique with the goal of measuring local mechanical and biological responses of articular cartilage under dynamic loading conditions. The details of the compression system and results of a pilot study are presented here. A 15% ramp compression at a rate of 0.003/s with a subsequent stress relaxation phase was applied to the cartilage explant samples. The extra cellular matrix was imaged throughout the entire thickness of the cartilage sample, and local tissue strains were measured during the compression and relaxation phase. The axial compressive strains in the middle and superficial zones of cartilage were observed to increase during the relaxation phase: this was a new finding, suggesting the importance of further investigations on the real-time local behavior of cartilage. The compression system showed promising results for investigating the dynamic, real-time mechanical response of articular cartilage, and can now be used to reveal the instantaneous mechanical and biological responses of chondrocytes in response to dynamic loading conditions.